Flipped classroom: An investigation into learner engagement during non-face-to-face components - KC Lee; Happy Goh; Jessie Teng; Kah Wei Wong (University of Johannesburg, 2020)
This paper investigated student engagement on the non-face-to-face component of the flipped approach in a critical thinking and writing class. Drawing from flipped approach and learner engagement literature and using an adapted version of Chi and Wylie's Interactive, Constructive, Active, Passive (ICAP) framework (2014), the study looked specifically at student engagement in non-face-to-face activities and tasks, namely video lectures, readings, tutorial materials, quizzes, and discussion forums. A total of 71 respondents were involved in the study. A self-perception survey designed to understand the level of student engagement was administered. Findings show that for activities of viewing e-lectures and doing assigned readings, most respondents displayed passive engagement, with a good proportion exhibiting active and constructive behaviours. However, there is an increased number of respondents who showed active and constructive engagement in going through materials in preparation for face-to-face tutorials, as well as in completing the online quizzes. Interactive engagement is not obvious. This study suggests that more strategic scaffolding provided for students could result in a higher level of effectiveness in learner engagement as well as a need to re-look at the design of the materials, activities, and tasks if the intent is to mediate interactive engagement. Keywords: Flipped classroom, ICAP framework, Online learning, Scaffolding, Student engagement How to cite this article: Lee, K.C., Goh, H., Teng, J. & Wong, K.W. 2020. Flipped classroom: An investigation into learner engagement during non-face-to-face components. Scholarship of Teaching and Learning in the South. 4(2): 118-137. https://doi.org/10.36615/sotls.v4i2.116. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/